Sciatic nerve: Non-union of its components and clinical implication - Baxla, Monica; Krishna, Hare; Tandon, Rati; Ganapathy, Arthi; Kaler, Saroj (International Journal of Research in Medical Sciences, 2019)
Background: Having prior anatomical knowledge of the anatomical variations is a must for the accurate and effective diagnosis of clinical conditions associated with the sciatic nerve. Sciatic nerve, the longest nerve in the human body has been of great interest for the clinicians and anatomists; though many studies have been conducted in the past to study its anatomical aspect. Till now high division or low formation of the sciatic nerve has been reported but this article highlights the non-union of the components of the sciatic nerve and its clinical outcomes. It had been observed that the common fibular and tibial nerve which arise separately from the sacral plexus remain separated throughout their course. They do not join to form the sciatic nerve. Non-union of the components can result in incomplete blockade of the nerve but selective blockade of one of the components can be done when needed. Aim of the study was to determine the level of formation and the level of division of the sciatic nerve. Methods: Sixty-two lower limbs were taken from the Department of Anatomy, AIIMS, New Delhi and gluteal region was observed for common fibular and tibial nerve and their joining to form the sciatic nerve. Results: Out of 62 lower limbs; 52 specimens showed formation within the pelvis but in 10 specimens the sciatic nerve did not form at any point. Division of the nerve in 52 specimens were at various levels on the posterior aspect of thigh. Conclusions: While giving anaesthesia it’s important to know the formation as well as division of the nerve for an effective lower limb block for various surgical interventions and in case of non union of tibial and common fibular nerve to form the sciatic nerve individual nerve block can be given.